Electronic identity cards in Spanish-speaking countries - K. R. Buynova (Ибероамериканские тетради, 2015)
The article summarizes the regional differences in the usage of the terms of the bureaucratic apparatus basing on the analysis of electronica IDs in the twenty countries where Spanish is the primary language.